Changes in Upper Airway Dimensions Following Orthodontic Treatment of Skeletal Class II Malocclusion with Twin Block Appliance: A Systematic Review - Roshan Noor Mohamed; Sakeenabi Basha; Yousef Al-Thomali (Turkish Journal of Orthodontics, 2020)

(untitled)
Objective:This systematic review intends to evaluate the dimensional changes in upper airway dimensions (UAD) of the respiratory tract subsequent to orthodontic treatment of skeletal Class II malocclusion with Twin Block Appliance (TBA).Methods:The quality of reporting systematic reviews and meta-analyses was decided by the PRISMA standards with PROSPERO registration number CRD42017060317. The systematic search included EMBASE, MEDLINE, Psych INFO, Scopus, CINAHL, and other reference journals and review articles. The article search was performed from March 2017 until November 2017. Cochrane's risk of bias in non-randomized studies – of interventions (ROBINS-I) was used to grade the methodological quality of the included studies.Results:The screening procedure identified 302 studies, among which seven studies satisfied the inclusion criteria for eligibility. The UAD at the pretreatment time varied from 7.2 mm to 41.9 mm with a mean of 14.16 mm. The post-treatment change in UAD ranged from 8.2 mm to 43.7 mm with a mean of 15.6 mm.Conclusion:There was a significant increase in UAD following the TBA treatment in the patient group as compared to the control group.